Perfil microbiológico e estabilidade aeróbia em silagem de capim-tifton 85, a vácuo e sem vácuo, adicionados ou não inoculante microbiano - Weirich, Daiane Thais; Neres, Marcela Abbado; Hunoff, Camila Andrine; Ströher, Sandra Mara; Nath, Caroline Daiane; Sunahara, Samantha Mariana Monteiro; Sarto, Jaqueline Rocha Wobeto [UNESP]; Oldoni, Tatiane (PPUFU - Portal de Periódicos da Universidade Federal de Uberlândia, 2018)
This study aimed to evaluate the microbiological profile and aerobic stability of grass silage Tifton 85, with or without vacuum, and with or without microbial inoculants. The experimental design was completely randomized in a 2 x 2 factorial design, where the treatments included five replicates, with and without vacuum or addition of inoculants. The inoculum consisted of lactic acid bacteria (LAB), specifically Lactobacillus acidophilus, at a concentration of 3 x 109 CFU mL-1 per mL. The analyzed variables included the microbiological profile after opening the silage, as well as the aerobic stability at the time of opening on the sixth day of the silage’s exposure to oxygen. It was found that no variation occurred in the population of lactic acid bacteria between the applied treatments. The Bacillus population was lower irrespective of the inoculant application, since it was applied in vacuum. When the population of Clostridium was applied, there was a reduction in the inoculant population in the vacuum system compared to that of the non-vacuum system. Without applying the inoculant, there was also a reduction in the population of Clostridium in the non-vacuum system. The yeast population showed linear growth in all of the evaluated treatments from the first to the sixth day of exposure to air, which may have contributed to the high temperatures observed during the air exposure period. There was no growth of fungi in the silage during the period of exposure to oxygen. The breaking of the aerobic stability occurred from the 3rd day after opening the silage. The pH was below the level that is considered to be good for silage preservation at the time of opening. In addition, during the exposure to oxygen, the same phenomenon occurred with the temperature, which demonstrated a quadratic behavior during the study period. Under the conditions evaluated, Tifton 85 bermudagrass silage lost its stability after the third day of exposure to air.
Microbiological profile and aerobic stability of tifton 85 bermudagrass silage with or without vacuum and microbial inoculants
Keywords: Fermentation; Lactic acid bacteria; Temperature; Yeast